Enhancement Students' Mathematical Connection Ability and Self- Efficacy through Problem Based Learning - Nufus, Hayatun; Turmudi, Turmudi; Syafitri, Yoesrina Novia Vini (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
This research is motivated by the importance of mathematical connection skills and students' Self-Efficacy in learning mathematics. This study aims to examine the literature on mathematical connections and student Self-Efficacy through problem-based learning. Through a mathematical connection between material and other material, it is hoped that students can reach several aspects of problem-solving. Self-Efficacy is one of several character values that are cultivated in learning. To deal with a problem requires an attitude of confidence in one's abilities known as Self-Efficacy. This attitude can affect student motivation and performance in mathematics learning. Thus, mathematical connection ability and Self- Efficacy have an important role in mathematics learning. Data collection was carried out by reviewing research from experts in several journals. The data analysis technique was carried out qualitatively by quoting the appropriate opinions.